H2 regularity for the p(x)-Laplacian in two-dimensional convex domains - del Pezzo, Leandro Martin (2014)
In this paper we study the H2 global regularity for solutions of the p(x)-Laplacian in two-dimensional convex domains with Dirichlet boundary conditions. Here p:Ω→[p1, ∞) with p∈Lip(Ω-) and p1>1.